Novel MMSE design for joint MIMO processing in analog Network Coding schemes - Lu, Enoch; Jialing Li; I-Tai Lu (2010 4th International Conference on Signal Processing and Communication Systems, 2010)
A novel generalized iterative approach (GIA) is proposed for jointly designing the MMSE MIMO processors (precoders, relay processors and decoders) for the analog Network Coding scheme. The MMSE performance can be achieved for MIMO communication links with two end nodes and multiple relay nodes subject to either the per-node power constraint or the practical per-antenna power constraint. Numerical results show that the analog Network Coding scheme is more spectral and energy efficient than the conventional Direct Transmission (DT) scheme.